Morphological and dimensional characteristics of dental arch in children with beta thalassemia major - Disha Kumar; Anant Gopal Nigam; Nikhil Marwah; Puneet Goenka; Asmita Sharma (Wolters Kluwer Medknow Publications, 2018)
Background and Objectives: The aim of this study was to examine the arch dimensions of beta thalassemia major patients in comparison with normal individuals. Materials and Methods: Dental arch dimensions were compared between thalassemic patients and normal individuals in the age group of 12-16 years in the maxillary and mandibular arch corresponding to each other regarding age, sex and Angle's molar relationship. A total number of sixty cases in each group were taken. Maxillary and mandibular impressions were made with alginate for all the sixty participants in each group and poured with die stone. Measurement of inter incisor, inter canine, inter premolar and intermolar arch width, arch depth, right anterior, right posterior, left anterior, and left posterior arch length was carried out from each cast using digital Vernier caliper.Results: Unpaired t-test was used for comparison between the two groups. Statistically, a significant difference was found between the case and control groups in the maxillary arch in intercanine width, inter premolar width, intermolar width, right anterior arch length, right posterior arch length, and left anterior arch length. However, no statistically significant difference was found between the groups in inter incisor width, left posterior arch length, and arch depth in the maxillary arch. In the mandibular arch, statistically significant difference was found between the case and control groups in inter canine width, inter premolar width, inter molar width, and left anterior arch length. However, no statistically significant difference was found between the case and control groups in the mandibular arch in interincisor width, right anterior arch length, right posterior arch length, and left posterior arch length. Conclusion: Dental arch widths and arch lengths were significantly reduced in thalassemic patients as compared to normal individuals for the maxillary and mandibular arches.